2013
DOI: 10.1155/2013/579092
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Impulse control Disorders in Parkinson Disease

Abstract: Abstract.Aims: This review aims to evaluate the most recent evidence on the pathophysiology of impulse control disorders (ICDs) in Parkinson disease (PD) Methods: Computerised searches of Medline, Embase and PsycInfo, along with manual searches for grey literature, were conducted and resulted in a total of 16 studies suitable for review. Results: Evidence was divided into four categories: medication used in PD management, imaging studies, genetic analysis and subthalamic deep brain stimulation (STN-DBS). Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
12
0
5
Order By: Relevance
“…Although our PD samples were tested on dopaminergic medication, they still revealed signs of dopamine deficiency as indicated by a mean value of 17.05 in the motor part of the UPDRS. In addition, some of the medications are known to be associated with impulse control disorders in PD, as these aspects might have implications for emotion processing in patient population [ 72 - 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our PD samples were tested on dopaminergic medication, they still revealed signs of dopamine deficiency as indicated by a mean value of 17.05 in the motor part of the UPDRS. In addition, some of the medications are known to be associated with impulse control disorders in PD, as these aspects might have implications for emotion processing in patient population [ 72 - 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in rats, lesions or high frequency stimulations of the STN increase premature responses in different reaction time tasks and impair animal's ability to inhibit responses. Moreover, STN-DBS or subthalamotomy in Parkinson's disease can be associated with behavioural and psychiatric problems that reflect deficits in inhibitory control or with the appearance of impulse control disorders (see Jahanshahi et al, 2014;Balarajah & Cavanna, 2013). For instance, several studies in which go/no-go paradigms were used reported that STN-DBS impairs the ability to withhold responses on no-go trials (Hershey et al, 2004(Hershey et al, , 2010Ballanger et al, 2009;Georgiev et al, 2016; but see also van den Wildenberg et al, 2006).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…ICDs can manifest in a spectrum of behaviors, including hypersexuality, pathological gambling, compulsive buying, binge eating, hobbyism, and punding (Balarajah and Cavanna, 2013). ICDs represent a particular manifestation of dysfunction in impulse/action control; phenomenologically they involve both impulsive (with respect to response initiation) and compulsive (with respect to response termination) dimensions (Mosley and Marsh, 2015).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%